Behaliens : choreographic behavior - Sóley Ólafsdóttir 1999- (2022)
In this paper I will account for and reflect upon my choreographic work “Behaliens” as well as my working process towards it. The choreography was created as my Individual Project for my final year at the BA program, Contemporary Dance Practices at Iceland University of the Arts. The choreography was created as a trio, for a trio. A trio of three “behaliens”.being, myself; Sóley Ólafsdóttir, Bjartey Elín Hauksdóttir and Marta Ákadóttir. I will discuss my questions and theories that led me through the creative process, as well as my working methods in the dance studio, dealing with those theories and questions. I will contextualize my ideas and working methods through Andrew Hewitt’s writings on social choreography and the aesthetic continuum. In theory and practice looking at human’s behavior as conditioned through the experiences of seeing one’s subject self as a moldable object. In that regard reviewing the definition of self-objectification. A process of rediscovering our behavior as being conditioned by the means of one trying to conform, to fit in, thereby, our behavior becoming choreographic. a social choreography. As a result of having these ideas in mind for the creative and working process, I will reflect on composition. Looking at what principles construct the way we behave, and then seeing if I could apply those principles as a tool for composition, restricting myself with parameters. I reflect on behavior as a social phenomenon, how a community together creates a common understanding of how one should be, behave and be seen. Through what we discovered physically dealing with these ideas, the product, the performance, at last, the “behaliens” being seen. I will reflect on the “behaliens” in the performance appearing as “uncanny,” and contextualize my ideas through Andrew Benett and Nicholas Royale’s writings on the uncanny.